Website-based: smart goat farm monitoring cages - Dwinanda Hafid Wicaksana; Wella Wella (Universitas Ahmad Dahlan, 2025)
Goat farming holds significant profit potential due to high community demand for goat meat and its role in supporting national food security. To optimize its development, proper and efficient farm management is essential. This study aims to design a system for monitoring and improving goat farming by observing key environmental and animal health conditions, such as feed availability, temperature, humidity, and overall livestock health. The proposed system utilizes internet of things (IoT) technology and cloud storage to create a smart farm environment. Various IoT devices, including cameras, thermal sensors, and lighting equipment, are integrated and connected via Wi-Fi. These devices collect real-time data, which is then processed into informative analytics to monitor and support farm development. Through the use of IoT and cloud-based solutions, this system is expected to enable real-time supervision and create ideal, controlled conditions for goat farming, ultimately benefiting farmers.